The Relationship between Self Control and Students Narcissistic Tendency as Instagram Users in SMP N 2 Padang - Nur Asiah; Taufik Taufik; Firman Firman (Jurnal Neo Konseling, 2019)
This study is based on lot of the students who demonstrate self –existence on a social network especially instagram in order to get recognition. One of the factors alleged to affect it is self control. The purpose of this study is : 1. To describe the students narcissistic tendency as the instagram users, 2. To describe the students as instagram usel self control, and 3. To test the significance of self control relationships with the students narcissistic as instagram users. The study used a quantitative approach with a kind of correlational descriptive. The subject of this study is 115 of SMP 2 Padang students. The data analysed with a conventional technique and Pearson Product Moment Correlation formula. The result of the study are: 1. The students narcissistic tendency as instagram users are in pretty high category. 2. The students self-control are in the high category. 3. And there’s a significant negative connection between self control and the students narcissistic tendencies with coefficients of -0.717 and the significance of 0,000.